2006
DOI: 10.1091/mbc.e05-08-0768
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nature of Cleavage Bodies and Their Spatial Relationship to DDX1 Bodies, Cajal Bodies, and Gems

Abstract: DDX1 bodies, cleavage bodies, Cajal bodies (CBs), and gems are nuclear suborganelles that contain factors involved in RNA transcription and/or processing. Although all four nuclear bodies can exist as distinct entities, they often colocalize or overlap with each other. To better understand the relationship between these four nuclear bodies, we examined their spatial distribution as a function of the cell cycle. Here, we report that whereas DDX1 bodies, CBs and gems are present throughout interphase, CPSF-100-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 62 publications
2
47
0
Order By: Relevance
“…S5 in the supplemental material), suggesting that the reduced numbers of RPA foci observed upon DDX1 depletion following IR treatment are unlikely to be due to a role for DDX1 in replication. In agreement with this, we have previously shown that DDX1 does not form foci in cells treated with aphidicolin, cisplatin, or UV until 24 h posttreatment, when stalled replication forks eventually collapse and form DSBs (9,24).…”
Section: Ddx1 Contributes To Dsb Repair and Cell Survival Post-irsupporting
confidence: 84%
See 1 more Smart Citation
“…S5 in the supplemental material), suggesting that the reduced numbers of RPA foci observed upon DDX1 depletion following IR treatment are unlikely to be due to a role for DDX1 in replication. In agreement with this, we have previously shown that DDX1 does not form foci in cells treated with aphidicolin, cisplatin, or UV until 24 h posttreatment, when stalled replication forks eventually collapse and form DSBs (9,24).…”
Section: Ddx1 Contributes To Dsb Repair and Cell Survival Post-irsupporting
confidence: 84%
“…First, DNA replication stress, shown by others to induce R-loop formation (64,65), did not result in accumulation of DDX1 at chromatin (9,24). However, DDX1 foci were observed 24 h after replication disruption, when stalled replication forks eventually collapse and form DSBs.…”
Section: Discussionmentioning
confidence: 92%
“…DDX1, a helicase involved in transcription, 53,54 mRNA processing 55,56 and translation, 57 is upregulated in neuroblastoma and retinoblastoma cell lines and tumors.…”
Section: Cancer and Agingmentioning
confidence: 99%
“…In the human host, DDX1 (Fig. 4) functions in transcription, 53,54 premRNA processing 55,56 and mRNA translation. 57 It interacts with the oligomerization domain of HIV-1 Rev, 58 and promotes Revoligomerization on the RRE.…”
mentioning
confidence: 99%
“…This is reminiscent of the relationship between gems, Cajal bodies and cleavage bodies, all structures involved in steps of pre-mRNA processing. These bodies can occur as separate nuclear structures, but can be also be twinned or colocalised in some situations (Li et al, 2006). Intriguingly, given the spatial juxtaposition of KAKA foci and PML-NBs, both KAP1 and PML are proteins of the RBCC family.…”
Section: Krab Zfps Characterise a Novel Nuclear Bodymentioning
confidence: 99%